Odpowiedzi

2009-10-26T16:38:54+01:00
81x do trzeciej - 9x do kwadratu - 9x +1 =0
81x³-9x²-9x+1=0
9x²(9x-1)-(9x-1)=0
(9x-1)(9x²-1)=0
(9x-1)(3x-1)(3x+1)=0
zatem

9x-1=0 3x-1=0 3x+1=0
9x=1/:9 x=1/3 x=-1/3
x=1/9
  • Użytkownik Zadane
2009-10-26T16:39:35+01:00
81x³ - 9x² - 9x +1
9x²(9x-1)-1(9x-1)
9x²-1
9x²=1 [/:9]
x²=1/9
x=1/3
2009-10-26T16:42:28+01:00


81x do trzeciej - 9x do kwadratu - 9x +1 =
= 81x³-9x²-9x+1 = 0
9x²(9x-1)-(9x-1) = 0
(9x-1)(9x²-1 = 0
(9x-1)(3x-1)(3x+1) = 0
wiec

9x-1=0 3x-1 = 0 3x+1 = 0
9x=1/;9 x = 1/3 x = -1/3
x = 1/9
tak mi sie wydaje ale nie jestem pewien